98.9k views
5 votes
When p2 -4p is subtracted from p2+p-6 the result is blank. To get p-9 subtract blank fro. The result.?

User PeterPan
by
5.9k points

2 Answers

4 votes

(p^2+p-6)-(p^2-4p)=p^2+p-6-p^2+4p=5p-6\\\\(5p-6)-(p-9)=5p-6-p+9=4p+3
User Wizuriel
by
4.9k points
7 votes

Answer:

First question :

Here, the given problem,


p^2+p-6-(p^2-4p)


=p^2+p-6-p^2+4p


=p^2(1-1)+p(1+4)-6


=5p-6

Thus, the result is 5p -6.

Second question:

Let to get p-9 we need to subtract X from 5p-6,

I.e.


5p-6-X = p - 9


5p-6-p+9=X


\implies X = 4p + 3

Thus, the result would be 4p + 3.

User Tom Baxter
by
5.5k points